Clinical Profiles and Post-Surgical Outcomes of Ectopic Pregnancy: Experience of 60 Cases in Bangladesh (Journal of Current and Advance Medical Research, 2025)
Background: Ectopic pregnancy is a significant cause of morbidity in reproductive-age women.Objective: The purpose of the present study was to assess the various clinical presentations and outcomes of ectopic pregnancy.Methodology: This prospective cohort study was conducted among patients admitted to Maternal and Child Health Training Institute, Azimpur, Dhaka, Bangladesh from January 2022 to December 2023 for a period of two years. It involved the clinical evaluation of ectopic pregnancy cases, focusing on sociodemographic characteristics, clinical presentations, risk factors, examination findings, intraoperative observations, and the management provided to the patients.Results: Most of the 60 patients were aged 26 to 30 years (51.7%), with a mean age of 28.17±4.39 years. All patients had a history of amenorrhea, and the most common symptom was abdominal pain (93.3%). Syncopal attacks occurred in 48.3% of cases, and 38.3% had per vaginal bleeding. The primary risk factor was a history of previous abortions or menstrual regulation (48.3%), followed by pelvic infections (28.3%) and previous D&C (16.7%). The ampulla was the most common site for ectopic pregnancies (88.3%), with 65% of ectopic sacs in the fallopian tube and 35% ovarian. Most patients underwent salpingectomy (71.7%) and were managed by laparotomy (85%). A majority (88.3%) had a hospital stay of less than 7 days.Conclusion: In conclusion, prior abortions are a more significant etiological factor for ectopic pregnancy compared to previous pelvic infections.Journal of Current and Advance Medical Research, January 2024;11(1):22-27